Association of regulatory variants of dopamine β-hydroxylase with cognition and tardive dyskinesia in schizophrenia subjects. (March 2020) - Punchaichira, Toyanji J; Mukhopadhyay, Anirban; Kukshal, Prachi; Bhatia, Triptish; Deshpande, Smita N; Thelma, BK
Background: Dopamine-β-hydroxylase (DBH, EC 1.14.17.1), which converts dopamine to norepinephrine, is a candidate gene in neuropsychiatric diseases. Aim: To assess the effect of regulatory variants in DBH on schizophrenia and its endophenotypes –cognition and tardive dyskinesia. Methods: We tested association of functional variants 19bp Ins/Del, rs1989787 and rs1611115 in DBH with i) schizophrenia (1236 cases, 1136 controls), ii) tardive dyskinesia (83 positive, 162 negative) and iii) performance functions of cognition (357 cases, 306 controls) estimated by the Penn Computerized Neurocognitive Battery. Results: A modest haplotypic ( Ins -C; 19bp Ins/Del – rs1989787 C>T; p =0.04) association was observed with schizophrenia. We observed 39% reduction in activity of 19bp Del allele on luciferase assay. Analysis of covariance revealed interactions of tardive dyskinesia status and: i) 19bp Ins/Del (genotypic, p =0.04) and ii) rs1989787 and rs1611115 (combined genotypic, p =0.004) on Abnormal Involuntary Movement Scale total score. Association of rs1611115 with positive and negative syndrome scale (PANSS) total score ( p =0.05) and allelic/genotypic association with lower positive ( p =0.03/0.04), general psychopathology ( p =0.01/0.01) PANSS scales in tardive dyskinesia-positive; and allelic/genotypic ( p =0.02/0.05) with higher score of depressive factors in tardive dyskinesia-negative subgroups were observed. Analysis of covariance with continuous variable of cognition showed interaction of health status with: i) rs1989787 on accuracy and efficiency ( p =0.03) of abstraction and mental ﬂexibility; ii) rs1611115 on accuracy of working memory and emotion ( p =0.05); iii) 19bp Ins/Del on processing speed of emotion ( p =0.03). Allelic/genotypic association of rs1989787 with spatial ability ( p =0.02–0.05) among healthy controls; association of rs1611115 with Global Assessment Scale scores in the past month ( p =0.05) among schizophrenia subjects of cognition cohort was also observed. Conclusions: With modest genotype–phenotype correlations available for DBH variants, personalized treatment regimens based on DBH activity for ameliorating tardive dyskinesia and cognitive symptoms may be plausible.